Implementação de um sistema de monitoramento de transporte estudantil utilizando Arduino e Redes Zigbee - Leite, Jefferson John do Rêgo (Universidade Federal Rural do Semi-Árido, 2018)
Public transportation is one of the most widely used means of transportation around the world. As in some Brazilian universities this system is available for the locomotion of the student body to the university, as is the case of UFERSA - Campus Pau dos Ferros. Some problems inherent to the system, such as delays, changes in schedules and even change of routes end up causing damages to the students who make use of this means of transport. In order to minimize these problems, this work proposes a bus monitoring system, provided by UFERSA - Câmpus Pau dos Ferros, using the prototype board together with the XBee and GPS sensors. With such work in progress, it will be possible to verify the position of the bus and the transmission of this information to the users. This information is shared by means of a map showing the last position of the bus and its trajectory.
Keywords: Ônibus; Arduino; GPS; Xbee; Bus; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA